Use of nicotine replacement therapy in socioeconomically deprived young smokers: a community-based pilot randomised controlled trial. Issue 5 (22nd September 2006) - Roddy, Elin; Romilly, Nick; Challenger, Alison; Lewis, Sarah; Britton, John
Abstract : Background: Smoking is common in young people, particularly in disadvantaged groups, and continued smoking has a major impact on quality and quantity of life. Although many young smokers want to stop smoking, little is known about the design and effectiveness of cessation services for them. Objective: To determine whether nicotine replacement therapy (NRT) when combined with counselling is effective in young smokers in a deprived area of Nottingham, UK Methods and subjects: We surveyed smoking prevalence and attitudes to smoking and quitting in young people accessing an open access youth project in a deprived area of Nottingham, and used the information gained to design a community based smoking cessation service incorporating a randomised controlled trial of nicotine patches against placebo given in association with individual behavioural support. We resurveyed smoking prevalence among project attendees after completing the pilot study. Results: Of 264 young people surveyed (median age 14 years, range 11–21), 49% were regular smokers. A total of 98 young people were recruited and randomised to receive either active nicotine patches on a six week reducing dose regimen (49 participants), or placebo (49 participants). Adherence to therapy was low, the median duration being one week, and 63 participants did not attend any follow up. At four weeks, five subjects receiving active NRT and two receiving placebo were abstinent, and at 13 weeks none were. Adverse effects were more common in the active group but none were serious. Smoking prevalence among 246 youth project attendees surveyed after the trial was 44%. Conclusions: This study suggests that NRT in this context is unlikely to be effective in young smokers, not least because of low adherence to therapy. It also suggests that young smokers want help with smoking cessation, but that establishing the efficacy of smoking cessation services for young people who need them most will be very difficult.